PERAN ORANG TUA DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA SEKOLAH DASAR - Demu, Maria Margaretha A. T.; Lina, Virgilius Bate; Seda, Hermanus Yodison; Mone, Cinri; Kaku, Viktorianus (LPPM Institut Pendidikan Nusantara Global, 2023)
The formulation of the problems in this study were (1) what is the role of parents in educating children to read in the family in Ulupulu 1 Village, Nangaroro District, Nagekeo Regency? (2) what is the reading ability of elementary school age children in Ulupulu 1 Village, Nagaroro District, Negekeo Regency? (3) what is the role of parents in improving children's beginning reading skills in Ulupulu 1 Village, Nangaroro District, Nagekeo Regency? This study aims to: (1) the role of parents in educating children to read in the family. (2) the ability to read in Ulupulu 1 village, Nagaroro sub-district, Nagekeo district. (3) the role of parents in improving the early reading skills of elementary school aged children in Ulupulu 1 village, Nagaroro district, Nagekeo district. This research is a qualitative research. Because it is used to see the relationship between the role of parents and children's reading ability based on facts. The data collection technique is done by conducting in-depth interviews, observation, and documentation. The subjects of this study were parents and grade II elementary school students in Ulupulu I village, Nangaroro district, Nagekeo district in 2020 on the subject of